VALIDITY AND RELIABILITY OF INSTRUMENT TO MEASURE CLINICAL INDICATOR OF NURSING DIAGNOSIS: FATIGUE ON PATIENT UNDERTAKING HAEMODIALYSIS - Atika Dwi Astuti; Intansari Nurjannah; Sri Mulyani (Belitung Nursing Journal, 2018)
Background: Fatigue as nursing diagnosis is a common phenomenon in patient undertaking haemodialysis. There is, however, no clear instrument to measure the clinical indicators of this nursing diagnosis. Objectives: To measure the validity and reliability an instrument to measure clinical indicator in nursing diagnosis fatigue. Methods: Content Validity Index for Scale (S-CVI) and Point-Biserial Correlation were used to measure the validity of instrument. Cronbach Alpha Reliability was used for reliability of 72 patients undertaking haemodialysis. Results: S-CVI score was 1 on relevance, accuracy and clarity, 0.98 on simplicity and ambiguity. The Cronbach’s Alpha of the instrument was 0.675 which was considered reliable. Conclusion: The instrument to measure clinical indicators of nursing diagnoses fatigue has acceptable validity and reliability score in Indonesian, and it is recommended to be used in clinical setting.